Partnerstwo publiczno-prywatne w rozwoju infrastruktury służącej poprawie konkurencyjności gmin - Dziworska, Krystyna; Szczepaniak, Krzysztof (PPP's Infrastructure Development that Improves Local Governments Competitiveness, 2006)
Polish local governments should have a dynamic increase of expenditures on infrastructure fastens during the next 15 years to be competitive against the European Union regions. The World Bank estimates that coping with needs in this area requires expenditures of 21 mid euro. The weak condition of public finance in Poland does not give a chance for this challenge without using out of budget financial funds for investments. The projects realization in the formula of PPP permits 10 improve the quality of public service. The formula of PPP also helps to achieve better effectiveness of investment expenditures. It increases the chance for realization of more investment projects as well and it helps to improve the quality of available commune infrastructure
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 211-221